The Enhancing Work Quality and Customer Satisfaction in the Culinary Industry: A Case Study of CV. Cypher Food Indonesia - Diyan Putranto; Theresia Alveria P.S.A; Sopyan Adi; Anindita Gayatri; Barliani Dewi Setyawati; Albertus Banundoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the digital era, CV. Cypher Food Indonesia, a leading figure in the food and beverage industry, recognizes technology's profound impact on its operations. This study delves into the crucial role of the HRD department in enhancing waitresses' and baristas' performance through customized training. In the competitive culinary landscape, customer satisfaction is paramount, and CV. Cypher Food Indonesia is dedicated to equipping its workforce with the skills and ethics for exceptional service. The research employs an analytical descriptive approach, focusing on data analysis, presentation, and conclusions. It explores training program effectiveness, challenges, HR management implications, and implementation's impact. The study offers insights into job evaluations with recommendations for improvement. This research underscores the importance of ongoing training, emphasizing communication skills, feedback, technology integration, performance recognition, customer satisfaction, and employee empowerment.